Modeling and simulation of the aorta from clinical data using a fractional viscoelastic model and finite element method - Palomarez Ruiz, J. E.; Rodriguez Madrigal, M.; Castro Lugo, J. G.; Ramirez Treviño, A.; Rodriguez Soto, A. A. (Revista Mexicana de Ingenieria Biomedica, 2015)
The modeling and simulation of the biomechanical effects present in the aorta, give the health specialist a computational tool that can be used in the prevention and treatment of cardiovascular diseases. For that reason on this research a mathematical model was developed in order to implement digital dimensional simulations to analyze the mechanical behavior of arteries. First, its described the methodology used in the construction of the geometry of the artery based on images from a CT scan, next the necessary experimental tests to obtain mechanical parameters required by the model and finally his fractional order. Obtaining a finite element simulation where the areas of greatest stress concentration and the displacement field are identified. To obtain these results a novel formulation based on fractional order viscoelastic models was used and the values required for simulation were obtained through the complex modulus.